SPARC overexpression combined with radiation retards angiogenesis by suppressing VEGF-A via miR-410 in human neuroblastoma cells - Boyineni, Jerusha (D.A. Spandidos, 2016)
Neuroblastoma (NB) is the most common extracranial solid tumor in children and despite aggressive therapy survival rates remain low. One of the contributing factors for low survival rates is aggressive tumor angiogenesis, which is known to increase due to radiation, one of the standard therapies for neuroblastoma. Therefore, targeting tumor angiogenesis can be a viable add-on therapy for the treatment of neuroblastomas. In the present study, we demonstrate that overexpression of secreted protein acidic and rich in cysteine (SPARC) suppresses radiation induced angiogenesis in SK-N-BE(2) and NB1691 neuroblastoma cells. We observed that overexpression of SPARC in SK-N-BE(2) and NB1691 cells reduced radiation induced angiogenesis in an in vivo mouse dorsal skin model and an ex vivo chicken CAM (chorioallantoic-membrane) model and also reduced tumor size in subcutaneous mouse tumor models of NB. We also observed that SPARC overexpression reduces VEGF-A expression, in SK-N-BE(2) and NB1691 NB cells via miR-410, a VEGF-A targeting microRNA. SPARC overexpression alone or in combination with miR-410 and radiation was shown to be effective at reducing angiogenesis. Moreover, addition of miR-410 inhibitors reversed SPARC mediated inhibition of VEGF-A in NB1691 cells but not in SK-N-BE(2) NB cells. In conclusion, the present study demonstrates that the over-expression of SPARC in combination with radiation reduced tumor angiogenesis by downregulating VEGF-A via miR-410.